2012
DOI: 10.1093/bja/aer458
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intravenous morphine titration

Abstract: Relief of acute pain during the immediate postoperative period is an important task for anaesthetists. Morphine is widely used to control moderate-to-severe postoperative pain and the use of small i.v. boluses of morphine in the post-anaesthesia care unit allows a rapid titration of the dose needed for adequate pain relief. The essential principle of a titration regimen must be to adapt the morphine dose to the pain level. Although morphine would not appear to be the most appropriate choice for achieving rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 53 publications
1
93
0
3
Order By: Relevance
“…In some studies, a loading dose is administered followed by intravenous morphine titration every 5 minutes. [10,14,15] Other studies suggest starting treatment with a titration regimen in order to monitor and minimize adverse effects. [15,16] Morphine and fentanyl are among the most widely used and studied analgesics for trauma patients in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, a loading dose is administered followed by intravenous morphine titration every 5 minutes. [10,14,15] Other studies suggest starting treatment with a titration regimen in order to monitor and minimize adverse effects. [15,16] Morphine and fentanyl are among the most widely used and studied analgesics for trauma patients in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…[10,14,15] Other studies suggest starting treatment with a titration regimen in order to monitor and minimize adverse effects. [15,16] Morphine and fentanyl are among the most widely used and studied analgesics for trauma patients in the ED. A randomized double-blinded study comparing morphine and fentanyl in a prehospital setting demonstrated the two drugs were comparable in treating severe, acute pain in a prehospital setting during the first 30 minutes in spontaneous breathing patients.…”
Section: Discussionmentioning
confidence: 99%
“…memungkinkan penanganan nyeri yang cepat dan membatasi risiko overdosis. 1 American Society of Anestesiologists (ASA) menyatakan analgesia multimodal adalah kunci penanganan nyeri pascaoperasi. Penanganan nyeri yang baik akan meningkatkan hasil akhir pembedahan dengan mengurangi morbiditas dan mempercepat waktu pemulihan.…”
Section: Pendahuluanunclassified
“…This also makes a 5-min bolus interval safe in the PACU setting. Bearing this in mind, will help gauge when best to administer the second dose of morphine (2). Importantly, no case of respiratory depression following PACU discharge was identified in postoperative rounds designed to assess analgesia and identify complications.…”
mentioning
confidence: 99%
“…Prior to insertion, catheters may be trimmed to length, reducing the flow resistance and eliminating the need for coiling of excess catheter on the patient's skin surface. Our journal Pediatric Anesthesia has published case reports (1,2) where the length of line inserted has produced clinical complications, but there appears to be little guidance for prediction of length measurement in children.…”
mentioning
confidence: 99%